Pengaruh Bermain Finger Painting Terhadap Kreativitas Anak Usia 5-6 Tahun di PAUD Anak Soleha Palembang - Novi Astuti; Mardiah Astuti; Kurnia Dewi (Seulanga : Jurnal Pendidikan Anak, 2022)
This research is entitled "The Effect of Finger Painting Playing on the Creativity of Children aged 5-6 Years at PAUD Anak Soleha Palembang". As for the problem of this researcher, is there any effect of playing finger painting on the creativity of children aged 5-6 years in PAUD for children soleha Palembang. This type of research is Pre-experimental with One Group Pre test – Post test design (one group of subjects). The number of samples of children is 10 children consisting of 5 boys and 5 girls. Data collection techniques in the study used the initial observation method before being treated with finger painting learning, observation was used to collect data at the time of treatment, a score form test was carried out to determine the results after being given treatment and documentation in the form of photos. The data analysis technique used in this study used normality, homogeneity, and hypothesis tests. The results in this study obtained tcount = 8.9762 while dk = 10 + 10-2 = 18 with a 5% significance level so that t table = 1.734 was obtained because tcount = 8.9762> t table = 1.734 then the conclusion Ho is rejected, meaning that there is an influence playing finger painting on the creativity of children aged 5-6 years in PAUD for children soleha Palembang.